Does Facebook Use Predict College Students' Social Capital? A Replication of Ellison, Steinfield, and Lampe's (2007) Study Using the Original and More Recent Measures of Facebook Use and Social Capital. Issue 3 (27th May 2018) - Vanden Abeele, Mariek M. P.; Antheunis, Marjolijn L.; Pollmann, Monique M. H.; Schouten, Alexander P.; Liebrecht, Christine C.; van der Wijst, Per J.; van Amelsvoort, Marije A. A.; Bartels, Jos; Krahmer, Emiel J.; Maes, Fons A.
Abstract : In 2007 Ellison, Steinfield, and Lampe published an article on the positive association between Facebook use and social capital that started a decade of research on the social outcomes of social network site use. Although cited almost 9, 000 times, it received critique on the conceptualization and operationalization of Facebook use and social capital. In this study we replicate Ellison et al.'s study with original and alternative measures of social capital and Facebook use, thereby shedding light on the robustness, stability, and ecological validity of the original findings. We found that Facebook intensity positively predicts the original social capital measures, lending support to the validity of the original findings. Its relationship with structural measures, however, was weak for bridging and absent for bonding social capital.